Analisis Diversifikasi, Merger, dan Akuisisi Perusahaan - Warti, Risma; Audina, Dea Dara; Azizi, Adelia (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This research aims to analyze the diversification, mergers and acquisitions of manufacturing companies in Indonesia. The research method used is descriptive qualitative analysis with a literature study approach. The results show that the diversification analysis was developed with various objectives including increasing growth when the existing market/product has reached a maturity stage, maintaining stability by spreading the risk of profit fluctuations, increasing credibility in the capital market, to avoid dependence on a single item or product in circulation. in the market, fulfill the wishes of unsatisfied consumers, increase the attractiveness or interest of consumers, increase sales turnover, increase profits by using the same ingredients, and prevent consumer boredom. Keywords: Diversification, Mergers, and Company Acquisitions.